Economic origins of dictatorship and democracy - Acemoglu, Daron 1967- (Cambridge University Press, 2012)
This book develops a framework for analyzing the creation and consolidation of democracy. Different social groups prefer different political institutions because of the way they allocate political power and resources. Thus democracy is preferred by the majority of citizens, but opposed by elites. Dictatorship nevertheless is not stable when citizens can threaten social disorder and revolution. In response, when the costs of repression are sufficiently high and promises of concessions are not credible, elites may be forced to create democracy. By democratizing, elites credibly transfer political power to the citizens, ensuring social stability. Democracy consolidates when elites do not have strong incentive to overthrow it. These processes depend on (1) the strength of civil society, (2) the structure of political institutions, (3) the nature of political and economic crises, (4) the level of economic inequality, (5) the structure of the economy, and (6) the form and extent of globalization